NATURAL THEOLOGY IN A PLURALIST SOCIETY - Barrett, Peter (1997)
The meanings and aims of natural theology in its historical and contemporary phases are discussed.  As ‘the search for God through the exercise of reason and the observation of the world’, it complements the theology of revelation and constitutes the arena for the escalating dialogue between science and theology.  Such dialogue is prompted by the unfolding scientific picture of cosmic history - of an expanding and evolving universe, intelligible to the human mind, remarkably fine-tuned as though designed to allow the emergence and evolution of life into its hierarchy of complexity.
Keywords: Natural Theology; cosmic history; Natural Sciences; the cosmos